Unraveling the Obstacles to English Learning Among EFL Junior High School Students in the Parongpong Region - Katemba, Caroline Victorine (LPPM Universitas Advent Indonesia, 2024)
The study aimed to identify the primary obstacles encountered by junior high school students when learning English. Conducted as a cross-sectional survey, data were gathered from 102 9th-grade students in three public schools in Parongpong using a Likert questionnaire and analyzed through mean scores. Findings revealed that the key barriers included students' tendency to use their native language, grammar errors, limited speaking opportunities outside school, fear of making mistakes, and restricted vocabulary. Additionally, challenges arose from listening materials' speed and complexity, unfamiliar topics and words, as well as nervousness. Furthermore, hurdles in reading practice, complex text structures, idea generation, spelling, paragraph organization, grammar, teacher's limited use of learning media, and cognitive attitudes were observed. These findings are expected to aid teaching efforts, particularly in addressing barriers for EFL learners.